2012
DOI: 10.1063/1.4757398
|View full text |Cite
|
Sign up to set email alerts
|

Spring constant calibration of atomic force microscope cantilevers of arbitrary shape

Abstract: Compact metal probes: A solution for atomic force microscopy based tip-enhanced Raman spectroscopy Rev. Sci. Instrum. 83, 123708 (2012) Note: Radiofrequency scanning probe microscopy using vertically oriented cantilevers Rev. Sci. Instrum. 83, 126103 (2012) Switching spectroscopic measurement of surface potentials on ferroelectric surfaces via an open-loop Kelvin probe force microscopy method Appl. Phys. Lett. 101, 242906 (2012) Enhanced quality factors and force sensitivity by attaching magnetic bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
238
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(243 citation statements)
references
References 52 publications
3
238
0
2
Order By: Relevance
“…The averaging process of this calibration initiative naturally generates the hydrodynamic function of that cantilever type, embodied in (what we term here) its -coefficient, see Section II [11]. This immediately enables non-invasive calibration of AFM cantilevers (of any geometry) using the Sader method [11] -the method requires only the cantilever's resonant frequency and quality factor in air.…”
Section: Page 4 Of 25mentioning
confidence: 99%
See 1 more Smart Citation
“…The averaging process of this calibration initiative naturally generates the hydrodynamic function of that cantilever type, embodied in (what we term here) its -coefficient, see Section II [11]. This immediately enables non-invasive calibration of AFM cantilevers (of any geometry) using the Sader method [11] -the method requires only the cantilever's resonant frequency and quality factor in air.…”
Section: Page 4 Of 25mentioning
confidence: 99%
“…By combining and appropriately averaging this dataset through use of a recent theoretical development of the "Sader method", described in Refs. [11][12][13], uncertainty in the measured spring constant is systematically reduced.…”
Section: Page 4 Of 25mentioning
confidence: 99%
“…25 Thus, they are almost applicable to our cantilevers, which have an aspect ratio of 3.3 6 0.1. Consequently, we upgrade the model of Dupas et al by using the results of Sader et al 27 To do so, we need to translate the corrections in resonance frequencies from Eq.…”
mentioning
confidence: 99%
“…Sader et al 25 suggested that for a rectangular cantilever with an arbitrary aspect ratio, an imaginary component of the generalized hydrodynamic function H im can be approximated by a power law of the Reynolds number Re. The value of Re ¼ ð2pf q PBS b 2 Þ=ð4g PBS Þ, where g PBS is the viscosity of PBS.…”
mentioning
confidence: 99%
See 1 more Smart Citation